Comparative evaluation of antimicrobial, antibiofilm, antioxidant, antiviral, and antidiabetic activities of copper oxide nanoparticles biofabricated via Opuntia ficus indica - Mohamed K. Y. Soliman; Salem S. Salem (Scientific Reports)
Abstract The eco-friendly methods of synthesizing nanoparticles using plant extracts have garnered heightened attention. In recent years, copper oxide nanoparticles (CuO-NPs), have found utility in a variety of applications. This work reports the fabrication of CuO-NPs using watery extract of Opuntia ficus indica leaves as a stabilizing component. Different analyses were performed to characterize the produced CuO-NPs. The CuO-NPs produced were very stable, spherical, and about 65 nm in size. The antimicrobial potency of produced CuO-NPs was assessed against four Gram-positive and four Gram-negative pathogenic bacteria, as well as uniـcellular fungi, revealing inhibition-zones ranging from 18 to 24 mm and a minimum inhibitory concentration (MIC) between 62.5 and 500 µg/mL. The DPPH was utilised to investigate the free-radical scavenging ability of CuO-NPs at various concentrations, revealing a notable antioxidant capacity with an IC50 of 165.5 µg/ml. Moreover, CuO-NPs exhibited various antibiofilm activity versus S. aureus (MRSA) and P. aeruginosa inhibiting up to 59.3% and 89.4% at 200 µg/mL respectively. A molecular docking simulation revealed that CuO-NPs’ activity against bacterial strains may be due to beta-1,3-glucanase, with hydrophobic interactions with amino-acid residues in the active site. Moreover, CuO-NPs at a concentration of 125 µg/mL had a significant antiviral effect versus HAV and COXB4, with antiviral efficacy of 28.6% and 40.9%, respectively. Furthermore, the CuO-NPs at 1000 µg/mL exhibited 91.5% inhibition of α-amylase and 82.3% inhibition of α-glucosidase, therefore affirming their antidiabetic properties. Consequently, CuO-NPs have significant promise as an anti-inflammatory drug.